PENGARUH REPUTASI DAN UKURAN ORGANISASI TERHADAP KINERJA ORGANISASI NIRLABA DI INDONESIA - Kristin Wahyuningsih; Gustin Tanggulungan (Benefit: Jurnal Manajemen dan Bisnis, 2014)
The percentage of non-profit organization revenue allocation to program expense beside administratif expense is an indicator of organizational performance. This research aims to test the organizational characteristik of non-profit organization on  its performance. The samples consist of 9 non-profit organizations in Indonesia based on its financial statement from 2007 to 2010. Testing was conducted through a simple regression analysis and a regression intervening with the size of the organization as the intervening variable. The results shows that the organization’s reputation has significant and positive effect toward the size of the organization but negative effect towards the performance of organizations. The size of organization (total revenue and total assets) have significant and negative effect on the performance of non-profit organizations. The total revenues and total assets mediate perfectly the relationship between organization’s age and the performance of non-profit organization.